Fabrication of superwetting and antimicrobial wood-based mesoporous composite decorated with silver nanoparticles for purifying the polluted-water with oils, dyes and bacteria. Issue 2 (April 2022) - Du, Xiling; Shi, Lei; Pang, Jiuyin; Zheng, Huiwen; Shi, Junyou; Zhang, Ming
Abstract: Nowadays, organic pollutants (oils, aromatic compounds and dyes) released from the chemical industry are the main water pollutants, which greatly impact on the environment. To fix the defects of conventional materials such as single pollutant type, complicated process, low efficiency, high cost and difficult maintenance, etc., we present a novel, efficient, low-cost and green Ag@Wood composite for simultaneously purifying the wastewater containing multiple pollutants. Specifically, Ag + was reduced to Ag NP and successfully anchored onto Balsa wood. Ag@Wood product with best performance was obtained by using 0.05 mol L −1 AgNO3 to treat the wood (7 mm). As a filter, its degradation efficiency towards methylene blue (MB) reached up to 94.4%, displaying the excellent catalytic performance. Under simulated sunlight, its removal efficiency towards rhodamine B (RhB) was more than 81.3% when the Ag@Wood served as the dye adsorbent with photocatalysis. In addition, Ag@Wood has the excellent superhydrophilicity and underwater superoleophobicity (OCA = 153°), thus owns the remarkable separation efficiency for oil-in-water emulsions (even with high salinity and different pH). Notably, inactivation rates of E. coli, S. aureus and B. subtilis after Ag@Wood treatment reached up to 99.97%, 99.98% and 99.98%, which would bring us great environmental and economic benefits in its future practical application. Graphical Abstract: To solve the problems such as complicated process, low efficiency, relatively high cost, single pollutant treatment and difficult maintenance, etc., we present a simple, efficient, low-cost, and green Ag@Wood composite to purify the wastewater and simultaneously remove the multiple pollutants (e.g., aromatic dyes, oils and bacteria contaminants). ga1 Highlights: Triple-functional Ag@Wood nanocomposite for the complex wastewater purification was prepared. High-performance functional filters capable of removing bacteria, emitted dyes and oils contaminants were achieved. Thanks to the catalytic and antibacterial activities of Ag NP anchored to wood, various pollutants in water can be removed. Ag@Wood owns remarkable separation efficiency for oil-in-water emulsions (even with high salinity and different pH). Such Ag@Wood nanocomposite will bring us great environmental and economic benefits in its future practical application.